ANALISIS KUAT LENTUR BALOK BETON GGBFS BERTULANG BAMBU - Maulana, Endra; Chalid, Abdul (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Sangga Buana, 2024)
Steel is a non-renewable resource, and its increasing scarcity raises construction costs. Bamboo, a natural and renewable material, presents an alternative. Research on bamboo-reinforced concrete shows that bamboo’s potential strength is yet to be fully realized. To improve bamboo-reinforced concrete performance, treatments are needed to enhance adhesion between bamboo and concrete and to strengthen the composite material. The addition of Ground Granulated Blast Furnace Slag (GGBFS) aims to increase the strength of bamboo-reinforced concrete. This research explores the flexural strength differences between bamboo-reinforced GGBFS concrete beams and steel-reinforced GGBFS concrete beams, identifying the optimal GGBFS mixture composition for bamboo-reinforced beams. Using an experimental method, bending tests are conducted following SNI 4431:2011 standards. The variable tested is the compressive strength with GGBFS and bamboo reinforcement added. Both types of concrete undergo flexural strength testing. Results indicate that steel-reinforced beams are generally stronger, but bamboo-reinforced beams with a 30% GGBFS mixture achieve a strength of 2.64 MPa, nearly matching steel-reinforced beams at 2.66 MPa (99.73% of the steel strength). This finding suggests that a 30% GGBFS mixture can make bamboo-reinforced beams a viable alternative to steel in concrete construction.